2022
DOI: 10.1001/jamacardio.2021.4036
|View full text |Cite|
|
Sign up to set email alerts
|

Days at Home After Transcatheter vs Surgical Aortic Valve Replacement in Intermediate-Risk Patients

Abstract: Days at home, an emerging patient-centered outcome that quantifies time spent alive and out of health care facilities, has not been fully described in trials evaluating transcatheter aortic valve replacement (TAVR). We sought to compare the total number of days spent at home within the first year among intermediate-risk patients participating in a randomized clinical trial of TAVR with a self-expanding bioprosthesis vs surgical aortic valve replacement (SAVR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…[4][5][6] This emerging outcome may be important to individuals with severe aortic stenosis seeking to maximize postprocedural functional status and independence, and thus could potentially aid in the decision-making for the mode of aortic valve replacement. We previously examined DAH in high- 7 and intermediate-risk 8 patients using the U.S. CoreValve High Risk trial and the Surgical or Transcatheter Aortic-Valve Replacement in Intermediate-Risk Patients (SURTAVI) trial linked with Medicare claims and found that in the first year after the procedure, highrisk patients undergoing TAVR had ≈27 additional DAH compared with SAVR and that intermediate-risk patients had ≈15 more DAH compared with the surgical group. These differences were primarily due to longer postprocedural length of stay (LOS), excess mortality days, and more facility days after initial discharge, including time in skilled nursing facilities (SNFs).…”
mentioning
confidence: 99%
“…[4][5][6] This emerging outcome may be important to individuals with severe aortic stenosis seeking to maximize postprocedural functional status and independence, and thus could potentially aid in the decision-making for the mode of aortic valve replacement. We previously examined DAH in high- 7 and intermediate-risk 8 patients using the U.S. CoreValve High Risk trial and the Surgical or Transcatheter Aortic-Valve Replacement in Intermediate-Risk Patients (SURTAVI) trial linked with Medicare claims and found that in the first year after the procedure, highrisk patients undergoing TAVR had ≈27 additional DAH compared with SAVR and that intermediate-risk patients had ≈15 more DAH compared with the surgical group. These differences were primarily due to longer postprocedural length of stay (LOS), excess mortality days, and more facility days after initial discharge, including time in skilled nursing facilities (SNFs).…”
mentioning
confidence: 99%
“…We reported that "that intermediate-risk patients undergoing TAVR had approximately 9 more days at home 1 year after the procedure compared with those undergoing SAVR as a result of shorter index hospitalizations and fewer days in SNFs [skilled nursing facilities] and rehabilitation." 1 Unfortunately, our original analysis mistakenly included Medicare Advantage patients. This error was recognized during linkage of another data set to the Medicare Provider Analysis and Review file, which primarily includes Medicare fee-for-service patients but was discovered to also contain records for Medicare Advantage patients.…”
mentioning
confidence: 99%
“…To the Editor On behalf of my coauthors, I write to report important errors in our Research Letter, “Days at Home after Transcatheter vs Surgical Aortic Valve Replacement in Intermediate-Risk Patients” published Online First on October 20, 2021, and in the January 2022 issue of JAMA Cardiology. In this article, we reported the results of a post hoc analysis that was conducted between June 19, 2012, and June 30, 2018, of the Surgical or Transcatheter Aortic-Valve Replacement in Intermediate-Risk Patients (SURTAVI) trial linked to Medicare claims.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Research Letter titled “Days at Home after Transcatheter vs Surgical Aortic Valve Replacement in Intermediate-Risk Patients,” published Online First on October 20, 2021, and in the January 2022 issue of JAMA Cardiology , Medicare Advantage patients were mistakenly included in the analysis, which resulted in errors in the text, the Table, and the Figure. A Letter of Explanation has been published that explains the errors.…”
mentioning
confidence: 99%